A highly efficient polydopamine encapsulated clinical ICG theranostic nanoplatform for enhanced photothermal therapy of cervical cancer. Issue 18 (31st August 2022) - Du, Zhong; Ma, Rong; Chen, Shuang; Fan, Huimin; Heng, Youqiang; Yan, Ting; Alimu, Gulinigaer; Zhu, Lijun; Zhang, Xueliang; Alifu, Nuernisha; Ma, Cailing
Abstract : Photothermal therapy (PTT) is a safe and efficient anti-tumor treatment. Abstract : Photothermal therapy (PTT) is a safe and efficient anti-tumor treatment. A photothermal agent (PTA) with good biocompatibility and strong photothermal properties is of great importance for PTT. In this study, near-infrared (NIR) excitable clinical indocyanine green (ICG) was utilized as a PTA and further encapsulated by another PTA polydopamine (PDA) to form highly stable and efficient ICG@PDA nanoparticles (NPs). Then the ICG@PDA NPs were modified with methoxy polyethylene glycol amine (mPEG2000 -NH2 ) to form biocompatible ICG@PDA@PEG NPs. ICG@PDA@PEG NPs showed good water solubility and a spherical shape with an average size of 140 nm. Furthermore, the photothermal properties of ICG@PDA@PEG NPs were studied and excellent photothermal performance with a photothermal conversion efficiency of 43.7% under 808 nm laser irradiation was achieved. Then, the PTT properties of ICG@PDA@PEG NPs were confirmed on HeLa cells with an efficiency of 86.1%. Meanwhile, the in vivo biocompatibility and toxicity of ICG@PDA@PEG NPs were evaluated. No apparent in vivo toxicity was observed in 24 hours and 7 days. Next, in vivo PTT analysis was conducted for cervical tumor-bearing nude mice under 808 nm laser excitation. It showed a good anti-tumor effect in vivo . Thus, ICG@PDA@PEG NPs exhibited great potential for safe and efficient photothermal therapy in anti-tumor therapy.